Herbarium GB, University of Gothenburg - Claes Gustafsson (University of Gothenburg, 2021)
This database contains information from Gothenburg herbarium, Herbarium GB. It is a university-wide research infrastructure at the University of Gothenburg in the Department of Biology and Environmental Science.

The collections include about 1 million dried specimens from all corners of the world. The vascular plant collection is dominant and comprises about 750,000 specimens, while the other 250,000 specimens are mosses, algae, fungi, lichens and slime fungi.

The vascular plants contain a rich Nordic material, but also large collections from the Middle East, the Mediterranean and tropical South America. The latter collection reflects the department's more than 50 years of research activities in the region, especially within the Flora of Ecuador project, and which has resulted in the following families being particularly richly represented: Asteraceae, Cyclanthaceae, Heliconiaceae, Marantaceae, Rubiaceae and Scrophulariaceae.

Among the non-vascular plant collections, the mushroom collection is the largest and comprises about 100,000 specimens. This mainly consists of base fungi from Northern Europe, a large part of which are wood-degrading crust and bracket fungi. The herbarium also has collections of Psathyrellaceae, Hygrophoraceae, Lycoperdaceae, Inocybeaceae, Russulales and Boletales.

Assignments of coordinates to many localities are primarily generated through Sweden's Virtual Herbarium workflow (http://herbarium.emg.umu.se/), which includes transformations from Swedish coordinate systems as well as coordinates for centroids representing geographic or political units. The GBIF dataset is harvested from Sweden's Virtual Herbarium after these georeferencing protocols have been applied, indicated for each record in dwc:georeferenceRemarks where the relevant protocol has been documented.
Keywords: Occurrence; Specimen; Occurrence; OCCURRENCE; Biological Sciences; Biologi